Being ‘Muslim Waria’: Gender Nonconformity, Spiritual Belonging, and Ethical Ambiguity in a Javanese Pesantren - Danugroho, Agus; Rustinsyah, Rustinsyah; Adib, Muhammad; Assalamah, Tuhfatul Mubarokah (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
This article investigates how young transgender Muslims at Pesantren Waria Al-Fatah in Yogyakarta cultivate religious devotion through what is conceptualized as “sacred disobedience,” a mode of piety that reconciles obedience to God with nonconformity to gendered norms. Drawing on 18 months of ethnographic fieldwork, the study demonstrates that acts of worship among waria are not merely forms of resistance but expressions of sincere faith that transform marginality into moral creativity. Integrating perspectives from Islamic ethics and postcolonial queer theory, the article illustrates how ambiguity, belonging, and devotion constitute an alternative theology grounded in compassion. The pesantren is shown to function as a spiritual community in which love, sincerity, and faith reconfigure prevailing understandings of purity, sin, and personhood. Through this lived religiosity, waria Muslims contribute to a renewed vision of Islam that embraces human plurality as a manifestation of divine mercy and ethical possibility. “Sacred disobedience” operates as a lived and embodied theology, wherein devotion emerges through ethical ambiguity rather than mere conformity. Their lived religious practice challenges binary frameworks of orthodoxy and deviance, revealing that piety may arise precisely through tension. Consequently, Islamic boarding schools appear as microcosms of a more inclusive Islam grounded in compassion.